Guía para el diseño por integración de la red de acceso inalámbrico de telefonía celular 4G conforme a la normatividad y especificaciones de las redes de nueva generación. (2017)
The technological development in the network of wireless access 4G of the next generation networks (NGN) has allowed to improve the implementation of technological infrastructure that simplifies the deployment, it optimizes and to coverage the capacity of telecommunication networks; thus, it guarantees resources of network, contents and applications to the users at the highest levels of quality. The use of nodes LTE-Advanced (eNodeB) in the access network, it allows to work high speed of access, in order to improve the spectral efficiency, to reduce the relation of the delay, to optimize the bandwidth, to improve the connectivity across from heterogeneous networks and to offer a good quality of service. Consequently, the objective of this project is focus on giving a guide for the design for integration of the network of wireless access of cellular telephony 4G according to the regulations and specifications of the next generation networks. For that matter, this project identifies characteristics and technical specifications of the wireless technology 4G based on international standards, some of the providers of equipment and the parameters for the design and implementation of an access network of the fourth generation. Finally, the project provides a methodology of evaluation in order to determine in what grade the design of the access network was completed, it was based on each one of the environments of network such as coverage, capacity and applications as fundamental inputs for the design and the implementation of the access network of the wireless technology 4G.